PENGEMBANGAN TANAMAN OBAT DAN SIMPLISIA DI LAHAN PEKARANGAN PADA KELOMPOK TANI DI KELURAHAN BAROMBONG KOTA MAKASSAR - Hidrawati, Hidrawati; Karman, Nurliani; Amin, Asni (Jurnal BALIRESO, 2016)
People in the Village Barombong generally cultivate of medicinal plants in their garden. Cultivation of medicinal plants has not been done well and no post-harvest handling. The use of medicinal plants as a treatment has several advantages, among others: the side effects are relatively low compared to modern medicinals. However, plants have medicinal properties and pharmacological effects are variable. Utilization of medicinal plants is more effective and safe when used with dosage, time, method of use and the selection of materials appropriate to the disease. Based on those problems, our team do activities such asÂ (1) Introducing and training regarding the type, nature, pharmacological effects and benefits of medicinal plants for health, (2) training and demonstration plots on propagation techniques, fertilization and cultivation of medicinal plants; (3) Training and demonstration of method of making âsimplisiaâ and monitoring the growth of medicinal plants. Application of Science and Technology Program for the community through training and counseling introduction, cultivation of medicinal plants and simplicia to the group of women âAsokaâ in the Barombong village, Makassar. The program is considered successful because all of the planned program were run well and there were support and participation all of group members. This activity is expected to continues and extends in order to get attention from the local government to accustom the use of medicinal plants in the community and especially to mediate buyer or market of simplicia that will excite the people to develop medicinal plants.